An Empirical Analysis of Scarcity Strategies in the Automobile Industry - Balachander, Subramanian; Liu, Yan; Stock, Axel (Management Science, 2009)
Recent product introductions such as the Xbox 360, Sony Playstation 2, and PT Cruiser have been characterized by shortage of these products. Some experts have suggested that such scarcity can be a deliberate strategy for making the product more desirable. In this paper, we empirically examine the relationship between introductory inventory levels and consumer preference in the U.S. automobile industry and show that relative scarcity of a car at the time of introduction is associated with higher consumer preference for the product. Furthermore, we perform an empirical test of alternative theories about the rationale for introductory product scarcity. Specifically, we consider two theories of supplier-induced scarcity, namely the buying frenzy theory and the signaling theory, and an alternative theory that suggests that demand uncertainty causes introductory product scarcity. We find more support for the signaling theory of supplier-induced scarcity than the buying frenzy theory or the demand uncertainty theory in our analysis of the automobile market.